PREVALENCE OF ANXIETY SYMPTOMS ACCORDING TO THE HADS-A SCALE AND ASSOCIATED FACTORS AMONG INPATIENTS IN THE INTERNAL MEDICINE DEPARTMENT OF THAI BINH MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of anxiety symptoms using HADS-A and analyse selected associated factors among inpatients in the Internal Medicine Department, Thai Binh University of Medicine and Pharmacy Hospital, from November 2025 to April 2026.Subjects and methods: Cross-sectional descriptive study with analytical component among 250 inpatients aged ≥ 16 years, hospitalised ≥ 24 hours, and consenting to participate. Anxiety screened by HADS-A (cut-off ≥ 8). Pain reclassified as VAS < 5 and VAS ≥ 5. Data analysed with SPSS 25.0 using univariate logistic regression.Results: Anxiety symptom prevalence was 6.4% (borderline: 6%; definite: 0.4%). Mean HADS-A score 2.70 ± 2.45. Univariate analysis showed that having no current partner (OR = 3.34; 95% CI: 1.08-10.34; p = 0.044) and VAS ≥ 5 (OR = 6.17; 95% CI: 1.73-22.00; p = 0.013) were statistically associated with anxiety.Conclusion: Anxiety prevalence was lower than in several prior studies. VAS ≥ 5 pain and absence of a current partner were associated with anxiety.
Keywords: Anxiety, HADS-A, inpatients, pain, associated factors.